Treatment With an Angiopoietin-1 Mimetic Peptide Improves Cognitive Outcome in Rats With Vascular Dementia - Culmone, Lauren; Powell, Brianna; Landschoot-Ward, Julie; Zacharek, Alex; Gao, Huanjia; Findeis, Elizabeth L.; Malik, Ayesha; Lu, Mei; Chopp, Michael; Venkat, Poornima (Frontiers in Cellular Neuroscience, 2022)
Aim: In this study, we investigate the therapeutic effects of AV-001, a Tie2 receptor agonist, in middle-aged rats subjected to a multiple microinfarct (MMI) model of Vascular dementia (VaD). Methods: Male, 10–12-month-old, Wistar rats were divided into the following groups: Sham, MMI, MMI+1µg/Kg AV-001, MMI+3µg/Kg AV-001, MMI+6µg/Kg AV-001. AV-001 treatment was initiated 1 day after MMI and administered once daily (i.p). An investigator blinded to the groups conducted a battery of neuro-cognitive tests and rats were sacrificed at 6 weeks after MMI. Results: AV-001 treatment does not significantly alter blood pressure or heart rate at 6 weeks after MMI compared to the MMI control group. AV-001 treatment does not significantly alter body weight compared to baseline values. AV-001 treatment significantly decreases serum alanine aminotransferase, serum creatinine, and serum troponin I levels compared to the MMI control group; however, all values are within normal range. MMI induces mild neurological deficits indicated by low modified neurological severity scores (mNSS). Compared to the MMI group, 1µg/Kg AV-001 treatment group did not exhibit significantly different mNSS scores, while 3 and 6µg/Kg AV-001 treated groups exhibit significantly worse mNSS scores. MMI induces significant short and long-term memory loss, reduced preference for social novelty, and impaired spatial learning and memory compared to Sham group. Rats treated with 1µg/Kg AV-001 exhibit significantly improved short and long-term memory, increased preference for social novelty, and improved spatial learning and memory compared to MMI rats. Treatment with 3µg/Kg AV-001 improves short-term memory and preference for social novelty, while treatment with 6µg/Kg AV-001 improves only long-term memory compared to MMI rats. Thus, 1µg/Kg AV-001 treatment was selected as an optimal dose. Treatment of MMI with 1µg/Kg AV-001 significantly increases axon density, myelin density, myelin thickness, oligodendrogenesis, neurogenesis, synaptic protein expression, neuronal branching, and dendritic spine density in the brain compared to control MMI rats. Conclusions: AV-001 is a novel therapeutic agent to improve cognitive function and reduce white matter injury in middle aged-rats subjected to a MMI model of VaD. Treatment of MMI with 1µg/Kg AV-001 significantly improves cognitive function and increases axon density, remyelination, and neuroplasticity in the brain.